Pelatihan Penggunaan Aplikasi Geogebra sebagai Media Pembelajaran Inovatif pada Calon Guru Sekolah Dasar - Fauzi, Asri; Rahmatih, Aisa Nikmah; Ermiana, Ida; Umar, Umar; Handika, Ilham (LPPM Universitas Flores, 2023)
Innovative learning media is a form of developing learning media designed to provide a more interesting and interactive learning experience for students. Due to the importance of using innovative learning media, prospective elementary school teacher students must be equipped with various technology mastery skills to develop their abilities so that they can present a meaningful teaching and learning process. Meaningful learning certainly requires interactive media to support the implementation of classroom learning. One program that can be used is the GeoGebra program. The GeoGebra program is a computer or smartphone program that can visualize abstract mathematical material. The GeoGebra application shows that this program can be used as a bridge in delivering mathematics material so as to make it easier for educators in the teaching and learning process. The purpose of this training is to increase the knowledge and abilities of prospective elementary school teachers in designing and using GeoGebra in learning mathematics. In this service, an example of the material practised during the training is. The results of this service can be said to be successful, as seen from the enthusiasm of the participants in participating in the training. This is also marked from the results of the posttest questionnaire that 100% of participants are ready to use the GeoGebra application in developing learning media.